The Meaning of Signs in iPhone 15 Pro Advertisement Video - Putri, Indah Kurnia; Indrawati, Ni Luh Ketut Mas; Setianingsih, Ni Ketut Alit Ida (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes the iPhone 15 Pro advertisement video using a semiotic approach to uncover the meanings behind its verbal and visual signs. The research identifies various types of signs, including denotative elements like technical specifications the A17 PRO chip, Action button, and portrait features and connotative elements such as color schemes, imagery, and product design. Through Roland Barthes’ theory of denotation, connotation, and myth, the study explores how these signs convey messages of sophistication, versatility, and empowerment. The advertisement uses visual cues like sleek grey tones, white text, and yellow highlights to emphasize modernity and functionality, while verbal descriptions highlight technological innovation and user customization. Together, these elements create a myth of technological superiority, artistic empowerment, and social status associated with owning an iPhone 15 Pro. The findings demonstrate how Apple integrates semiotic strategies to appeal to consumers emotionally and culturally, reinforcing its brand identity as a leader in innovation and design. This research contributes to understanding how semiotic analysis can reveal the layered meanings in advertising and their impact on consumer perception.